Proton exchange membrane electrolysis water membrane electrode as well as preparation method and application thereof
By using non-precious metal-doped iridium ruthenium ternary composite catalyst and ultrasonic spraying process in the proton exchange membrane electrolytic water membrane electrode, the problems of high precious metal usage and large catalyst loading are solved, and efficient and economical hydrogen preparation is achieved.
Patent Information
- Application Number
- CN202311112163.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-02-28
AI Technical Summary
In the existing proton exchange membrane hydrogen production technology, the precious metal iridium used by the anode catalyst is high, and the catalyst loading in the membrane electrode is large, which limits the large-scale application of the technology.
The non-precious metal-doped iridium ruthenium ternary composite catalyst is used as the anode catalyst to prepare membrane electrodes through ultrasonic spraying process to reduce the amount of precious metals and improve the stability and oxygen evolution activity of the catalyst.
The amount of precious metals iridium and ruthenium is reduced, the oxygen evolution activity and stability of the membrane electrode is improved, the load of catalyst in the membrane electrode is reduced, and the economic and performance of the technology is improved.
Smart Images

Figure CN119530874A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the fields of hydrogen energy and chemical industry, and in particular, to a proton exchange membrane water electrolysis membrane electrode and a preparation method and application thereof. Background Art
[0002] Compared with alkaline water electrolysis technology, proton exchange membrane water electrolysis hydrogen production technology has the advantages of fast response speed, large current density, wide working load range, and high hydrogen purity. In particular, it has unparalleled advantages in the field of using renewable energy to generate electricity and then electrolyze water to produce hydrogen. It is the main way to obtain green hydrogen in the future. The anode catalyst is one of the key materials for proton exchange membrane water electrolysis hydrogen production and is the main rate-controlling step for PEM water electrolysis hydrogen production. At present, commercial PEM water electrolysis devices basically use iridium oxide or iridium black catalysts. The price of precious metal iridium is expensive (~1,000 yuan / g), and the dosage reaches 1-2 mg / cm 2 Therefore, reducing the amount of iridium in the anode is one of the important breakthroughs for the large-scale application of PEM water electrolysis. On the one hand, it is necessary to reduce the content of precious metal iridium in the catalyst, and on the other hand, it is necessary to reduce the loading of the catalyst in the membrane electrode. Compared with Ir, Ru has higher electrochemical intrinsic activity, but poorer stability and cannot meet commercial requirements. However, IrRu composite catalyst can take into account both the high stability of Ir catalyst and the high activity of Ru catalyst. SnO 2 、TiO 2 It has good oxidation resistance and corrosion resistance, and is cheap. However, the catalytic layer prepared by the scraping process currently used in membrane electrode preparation is relatively thick, resulting in a large catalyst loading in the membrane electrode. Summary of the invention
[0003] The purpose of the present disclosure is to provide a proton exchange membrane water electrolysis membrane electrode and a preparation method and application. The membrane electrode uses a non-precious metal-doped iridium-ruthenium ternary composite catalyst as an anode catalyst. Compared with commercial iridium oxide catalysts, the amount of precious metals used can be reduced, and it has excellent stability and high oxygen evolution activity; at the same time, the catalyst loading in the membrane electrode can be reduced.
[0004] In order to achieve the above-mentioned object, the first aspect of the present disclosure provides a proton exchange membrane water electrolysis membrane electrode, the membrane electrode comprises an anode catalyst layer, the anode catalyst layer contains a ternary composite catalyst of iridium and ruthenium, the ternary composite catalyst comprises iridium, ruthenium and non-precious metal elements, and the XRD spectrum of the ternary composite catalyst only shows an amorphous peak package at 25-40°;
[0005] Wherein, the non-precious metal element includes one or both of tin and titanium.
[0006] Optionally, the O1s characteristic peak of the XPS spectrum of the ternary composite catalyst includes a MO characteristic peak and an M-OH characteristic peak, and B defined by the following formula (1) 0 Any value between 0.2 and 0.5;
[0007] B 0 =B 1 / (B 1 +B 2 ) Formula (1);
[0008] Among them, B 1 is the peak area of the M-OH characteristic peak in the XPS spectrum of the ternary composite catalyst, B 2 It is the peak area of the MO characteristic peak in the XPS spectrum of the ternary composite catalyst.
[0009] Optionally, the BET specific surface area of the ternary composite catalyst is 50 to 80 m 2 / g, particle size is 2 to 10 nm.
[0010] Optionally, the XRD spectrum of the ternary composite catalyst does not have crystal plane diffraction peaks of iridium dioxide, ruthenium dioxide and non-precious metal oxides.
[0011] Optionally, the composition of the ternary composite catalyst includes, relative to the total molar number of metal elements, the molar number of Ir is 0.4-0.6, and the molar number of Ru is 0.1-0.2.
[0012] Optionally, the ternary composite catalyst comprises an iridium-ruthenium-titanium ternary composite catalyst, and the chemical composition of the iridium-ruthenium-titanium ternary composite catalyst is Ir x Ru y Ti 1-x-y O 2 ; Where x is any value between 0.4 and 0.5, and y is any value between 0.1 and 0.2;
[0013] The BET specific surface area of the iridium, ruthenium and titanium ternary composite catalyst is 50 to 60 m 2 / g, particle size is 2~10nm;
[0014] The XPS spectrum of the iridium, ruthenium and titanium ternary composite catalyst is B 0 Any value between 0.2 and 0.3;
[0015] The XRD spectrum of the iridium, ruthenium and titanium ternary composite catalyst only shows an amorphous peak package at 30-40 degrees.
[0016] Optionally, the ternary composite catalyst comprises an iridium-ruthenium-tin ternary composite catalyst, and the chemical composition of the iridium-ruthenium-tin ternary composite catalyst is Ir m Run Sn 1-m-n O 2 ; Wherein, m is any value between 0.4 and 0.6, and n is any value between 0.1 and 0.2;
[0017] The BET specific surface area of the iridium, ruthenium, and tin ternary composite catalyst is 60 to 80 m 2 / g, particle size is 3-8nm;
[0018] The XPS spectrum of the iridium, ruthenium, and tin ternary composite catalyst is B 0 Any value between 0.4 and 0.5;
[0019] The XRD spectrum of the iridium, ruthenium and tin ternary composite catalyst only shows an amorphous peak package between 25° and 40°.
[0020] Optionally, the iridium loading in the anode catalyst layer is 0.1 to 0.5 mg / cm 2 ; The ruthenium loading is 0.01~0.06mg / cm 2 .
[0021] Optionally, the membrane electrode further includes a proton exchange membrane and a cathode catalyst layer, and the anode catalyst layer and the cathode catalyst layer are stacked on both sides of the proton exchange membrane, respectively.
[0022] The second aspect of the present disclosure provides a method for preparing the proton exchange membrane water electrolysis membrane electrode according to the first aspect of the present disclosure, the method comprising the following steps:
[0023] An anode catalyst layer containing the ternary composite catalyst is formed on the first main surface of the proton exchange membrane; a cathode catalyst layer is formed on the second main surface of the proton exchange membrane; and the obtained membrane electrode precursor is subjected to hot pressing treatment.
[0024] Optionally, the step of forming the anode catalyst layer includes: preparing an anode catalyst layer slurry containing the ternary composite catalyst and performing a first ultrasound; spraying the anode catalyst layer slurry on the first main surface of the proton exchange membrane by ultrasonic spraying;
[0025] The step of forming the cathode catalyst layer comprises: preparing cathode catalyst layer slurry and performing a second ultrasound; spraying the cathode catalyst layer slurry on the second main surface of the proton exchange membrane by ultrasonic spraying;
[0026] The anode catalyst layer slurry includes a ternary composite catalyst, a Nafion solution and a dispersant solution; wherein, in the anode catalyst layer slurry, the mass fraction of the ternary composite catalyst is 0.1-2wt%, preferably 0.5-1wt%; the mass fraction of the Nafion solution is 5-12%, preferably 9-11%; the dispersant solution is a mixed solution of water and isopropanol; the volume fraction of the isopropanol in the mixed solution is 60-80%, preferably 70-75%.
[0027] Optionally, the first ultrasonic conditions include: ultrasonic time of 20 to 60 minutes, ultrasonic power of 600 to 900 W;
[0028] The second ultrasonic conditions include: ultrasonic time of 20 to 60 minutes, ultrasonic power of 600 to 900W;
[0029] The conditions of the hot pressing treatment include: a hot pressing temperature of 100 to 130° C., a hot pressing pressure of 1 to 10 bar, and a hot pressing time of 1 to 3 minutes.
[0030] Optionally, the ternary composite catalyst is prepared by the following steps:
[0031] S1, mixing an iridium source, a ruthenium source, a non-precious metal source, a complexing agent and water, and reacting the resulting mixture to obtain a first material; wherein the pH of the mixture is 5 to 10, and the complexing agent is selected from C4 to C8 organic polyacids and soluble salts of C4 to C8 organic polyacids;
[0032] S2, separating the water in the first material to obtain a ternary composite catalyst precursor;
[0033] S3. calcining the ternary composite catalyst precursor in an oxygen-containing atmosphere.
[0034] Optionally, in step S1, the molar ratio of the iridium source calculated as iridium, the non-precious metal source calculated as non-precious metal, and the ruthenium source calculated as ruthenium is (2-6): (1-5): 1;
[0035] In step S1, the reaction conditions include: temperature of 30-80°C, reaction time of 0.5-4h; Optionally, in step S1, the pH of the mixed material is 6-8;
[0036] In step S3, the conditions of the calcination treatment include: a calcination temperature of 300 to 450° C.; and a calcination time of 1 to 5 hours.
[0037] Optionally, step S1 includes the following steps:
[0038] S1-1, mixing the iridium source, the first complexing agent and water for the first time and adjusting the pH to 5-10 to obtain a first mixture;
[0039] S1-2, mixing the ruthenium source, the second complexing agent and water for a second time and adjusting the pH to 5 to 10 to obtain a second mixture;
[0040] S1-3, mixing the non-metal source, the third complexing agent and water for a third time and adjusting the pH to 5 to 10 to obtain a third mixture;
[0041] S1-4, mixing the first mixture, the second mixture and the third mixture to obtain the mixed material.
[0042] Optionally, the iridium source is selected from one or more of chloroiridic acid and chloroiridic acid alkali metal salts; preferably, the chloroiridic acid alkali metal salt is selected from one or both of potassium chloroiridate and sodium chloroiridate;
[0043] The ruthenium source is a soluble salt of ruthenium, preferably one or both of ruthenium trichloride and ruthenium acetate;
[0044] The non-metallic source includes one or both of a titanium source and a tin source; the titanium source is a soluble salt of titanium, preferably one or both of titanyl sulfate or titanium sulfate; the tin source is a soluble salt of tin and / or a soluble alkali metal stannate, preferably one or both of tin tetrachloride or sodium stannate;
[0045] The first complexing agent, the second complexing agent and the third complexing agent are the same or different, and are independently selected from one or more of citric acid, tartaric acid, malic acid, succinic acid, sodium citrate, sodium tartrate, sodium malate and sodium succinate;
[0046] Preferably, the molar ratio of the first complexing agent to the iridium source is 1.5 to 2.5:1;
[0047] Preferably, the molar ratio of the second complexing agent to the ruthenium source calculated as ruthenium is 1 to 2:1;
[0048] Preferably, the molar ratio of the third complexing agent to the non-precious metal source calculated as non-precious metal is 1.5 to 3:1.
[0049] The third aspect of the present disclosure provides the membrane electrode described in the first aspect of the present disclosure for use in a proton exchange membrane water electrolysis process.
[0050] Through the above technical scheme, the present invention adopts a non-precious metal-doped iridium-ruthenium ternary composite catalyst as an anode catalyst. The ternary composite catalyst contains iridium, ruthenium and non-precious metal elements, and only an amorphous peak package appears in the XRD spectrum, and there is no obvious crystalline diffraction peak; compared with the commercial iridium oxide catalyst, a small amount of highly active precious metal ruthenium is introduced, which improves the oxygen evolution activity of the catalyst while taking into account excellent stability; improves the utilization rate of precious metals iridium and ruthenium, and reduces the content of precious metals in the catalyst.
[0051] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0053] Figure 1 It is a membrane electrode current-voltage test curve diagram of Example 2 and Comparative Example 1. DETAILED DESCRIPTION
[0054] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.
[0055] The first aspect of the present disclosure provides a proton exchange membrane water electrolysis membrane electrode, the membrane electrode comprising an anode catalyst layer, the anode catalyst layer comprising a ternary composite catalyst containing iridium and ruthenium, the ternary composite catalyst comprising iridium, ruthenium and non-precious metal elements, the XRD spectrum of the ternary composite catalyst only showing an amorphous peak package at 25-40°;
[0056] Wherein, the non-precious metal element includes one or both of tin and titanium.
[0057] The present invention discloses a non-precious metal-doped iridium-ruthenium ternary composite catalyst as an anode catalyst. The ternary composite catalyst comprises iridium, ruthenium and non-precious metal elements. The XRD spectrum shows an amorphous peak package at only 25 to 40°, and there are no crystal plane diffraction peaks of iridium dioxide, ruthenium dioxide and non-precious metal oxides. Compared with commercial iridium oxide catalysts, the amount of highly active precious metals is reduced, the oxygen evolution activity of the catalyst is improved, and the stability of the catalyst is taken into account. The ternary composite catalyst has the characteristics of long-range disorder, can expose more active sites, and has high flexibility. The active sites can be transformed into any shape during the catalytic reaction, thereby improving the activity of the active sites.
[0058] In the present disclosure, "peak envelope" in the XRD spectrum refers to other forms of protrusions that appear in the XRD spectrum in addition to the obvious and sharp characteristic peaks conventionally recognized by technicians in this field. The "peak envelope" generally has the characteristics of low intensity and large width.
[0059] According to one embodiment of the present disclosure, the XRD spectrum of the ternary composite catalyst does not have crystal plane diffraction peaks of iridium dioxide, ruthenium dioxide and non-precious metal oxides. In the ternary composite catalyst provided by the present disclosure, the iridium element, the ruthenium element and the non-precious metal element exist in the form of amorphous oxides, and the crystal plane diffraction peaks of the three substances of iridium dioxide, ruthenium dioxide and non-precious metal oxides do not appear in the XRD spectrum.
[0060] According to one embodiment of the present disclosure, the chemical composition of the ternary composite catalyst includes, relative to the total molar number of metal elements, the molar number of Ir is 0.4-0.6, and the molar number of Ru is 0.1-0.2. x Ru y Z 1-x-y O 2 ; Wherein, Z includes one or two of Sn and Ti; x is any value between 0.4 and 0.6, and y is any value between 0.1 and 0.2.
[0061] According to one embodiment of the present disclosure, the O1s characteristic peak of the XPS spectrum of the ternary composite catalyst contains a MO characteristic peak and an M-OH characteristic peak, and B defined as follows: 0 Any value between 0.2 and 0.5;
[0062] B 0 =B 1 / (B 1 +B 2 ) Formula (1);
[0063] Among them, B 1 is the peak area of the M-OH characteristic peak in the XPS spectrum of the ternary composite catalyst, B 2 is the peak area of the MO characteristic peak in the XPS spectrum of the ternary composite catalyst. The inventors have found in experiments that when the B 1 / (B 1 +B 2 ) ratio is within the range of this embodiment, it can have a lower overpotential and a higher oxygen evolution activity; it further makes the decomposition voltage of the membrane electrode lower, the loading amount of the precious metal lower, the precious metal usage of the membrane electrode low, and the performance good.
[0064] According to one embodiment of the present disclosure, the BET specific surface area of the ternary composite catalyst is 50 to 80 m 2 / g, and the particle size is 2 to 10 nm. In the present disclosure, the particle size of the catalyst particles refers to the particle size of the catalyst particles measured by transmission electron microscopy. For example, "the particle size of the catalyst particles is 2 to 10 nm" means that the particle size of each particle in the transmission electron microscopy spectrum of the catalyst particles is within the range of 2 to 10 nm.
[0065] According to one embodiment of the present disclosure, the ternary composite catalyst comprises an iridium ruthenium titanium ternary composite catalyst, and the chemical composition of the iridium ruthenium titanium ternary composite catalyst is Ir x Ru y Ti 1-x-y O 2 ; wherein x is any value between 0.4 and 0.5, and y is any value between 0.1 and 0.2; the BET specific surface area of the iridium ruthenium titanium ternary composite catalyst is 50 to 60 m 2 / g, the particle size is 2 to 10 nm, preferably 3 to 6 nm; the B 0 is any value between 0.2 and 0.3; the XRD spectrum of the iridium, ruthenium and titanium ternary composite catalyst only shows an amorphous peak package at 30 to 40°, and the crystal plane diffraction peaks of the three substances of iridium dioxide, ruthenium dioxide and titanium dioxide do not appear in the XRD spectrum of the iridium, ruthenium and titanium ternary composite catalyst. In the present disclosure, the chemical composition of the catalyst is determined by X-ray fluorescence analysis (XRF analysis). The chemical composition of the catalyst is consistent with the raw material addition ratio during preparation. The chemical composition described in the present disclosure is only used as a schematic representation.
[0066] According to one embodiment of the present disclosure, the ternary composite catalyst comprises an iridium, ruthenium, and tin ternary composite catalyst, wherein the chemical composition of the iridium, ruthenium, and tin ternary composite catalyst is Ir m Ru n Sn 1-m-n O 2 ; wherein m is any value between 0.4 and 0.6, and n is any value between 0.1 and 0.2; the BET specific surface area of the iridium, ruthenium, and tin ternary composite catalyst is 60 to 80 m 2 / g, the particle size is 3 to 8 nm, preferably 4 to 6 nm; the B 0 is any value between 0.4 and 0.5; the XRD spectrum of the iridium ruthenium tin composite catalyst only shows an amorphous peak between 25 and 40°, and there is no IrO in the XRD spectrum of the iridium ruthenium tin composite catalyst 2 、RuO 2 and SnO 2 diffraction peaks of the crystal plane.
[0067] According to one embodiment of the present disclosure, the iridium loading in the anode catalyst layer is 0.1 to 0.5 mg / cm2 ; The ruthenium loading is 0.01~0.06mg / cm 2 .
[0068] According to one embodiment of the present disclosure, the membrane electrode further includes a proton exchange membrane and a cathode catalyst layer, and the anode catalyst layer and the cathode catalyst layer are respectively stacked on both sides of the proton exchange membrane. The proton exchange membrane can be a proton exchange membrane well known to those skilled in the art, such as Nafion 117; the cathode catalyst can be a cathode catalyst well known to those skilled in the art, such as a Pt / C catalyst, and the Pt loading can be 20 to 40 wt%.
[0069] The second aspect of the present disclosure provides a method for preparing the proton exchange membrane water electrolysis membrane electrode according to the first aspect of the present disclosure, the method comprising the following steps:
[0070] An anode catalyst layer containing the ternary composite catalyst is formed on the first main surface of the proton exchange membrane; a cathode catalyst layer is formed on the second main surface of the proton exchange membrane; and the obtained membrane electrode precursor is subjected to hot pressing treatment.
[0071] According to one embodiment of the present disclosure, the step of forming the anode catalyst layer includes: preparing an anode catalyst layer slurry containing the ternary composite catalyst and performing a first ultrasound; spraying the anode catalyst layer slurry on the first main surface of the proton exchange membrane by ultrasonic spraying;
[0072] The step of forming the cathode catalyst layer comprises: preparing the cathode catalyst layer slurry and performing a second ultrasound; spraying the cathode catalyst layer slurry on the second main surface of the proton exchange membrane by ultrasonic spraying. The present invention adopts a non-precious metal-doped iridium-ruthenium ternary composite catalyst as an anode catalyst, and adopts an ultrasonic spraying process to prepare a membrane electrode, further improving the performance and economy of the membrane electrode, so that the prepared membrane electrode has the characteristics of low precious metal loading, high precious metal mass specific activity, and high performance; at a current density of 2A / cm 2 When the decomposition voltage is only 1.81V.
[0073] According to one embodiment of the present disclosure, the anode catalyst layer slurry includes a ternary composite catalyst, a Nafion solution and a dispersant solution; wherein, in the anode catalyst layer slurry, the mass fraction of the ternary composite catalyst is 0.1-2wt%, preferably 0.5-1wt%; the mass fraction of the Nafion solution is 5-12%, preferably 9-11%; the dispersant solution is a mixed solution of water and isopropanol; the volume fraction of the isopropanol in the mixed solution is 60-80%, preferably 70-75%.
[0074] According to an embodiment of the present disclosure, the first ultrasonic conditions include: ultrasonic time of 20 to 60 minutes, ultrasonic power of 600 to 900 W;
[0075] The second ultrasonic conditions include: ultrasonic time of 20 to 60 minutes, ultrasonic power of 600 to 900W;
[0076] The conditions of the hot pressing treatment include: the hot pressing temperature is 100-130° C., and the hot pressing pressure is 1-10 bar.
[0077] According to one embodiment of the present disclosure, configuring the anode catalyst layer slurry includes the following steps: adding a ternary composite catalyst, water, isopropanol, and Nafion in this order, and then performing a first ultrasonic treatment.
[0078] According to one embodiment of the present disclosure, configuring the cathode catalyst layer slurry includes the following steps: adding cathode catalyst, water, isopropanol, and Nafion in sequence, and then performing a second ultrasound; in the cathode catalyst layer slurry, the mass fraction of the cathode catalyst is 0.1-1%, and the mass fraction of Nafion is 20-30%.
[0079] According to one embodiment of the present disclosure, the ultrasonic spraying includes being carried out on a negative pressure vacuum table, the temperature of the vacuum table can be 50-90°C, the ultrasonic nozzle is equipped with a 40KHz 130W ultrasonic atomizer, the total amount of slurry sprayed is calculated according to the area of the membrane electrode and the mass fraction of the catalyst, the mass of the membrane electrode is weighed before and after spraying on each side, and the mass difference is the total mass of the catalyst layer sprayed on the surface of the membrane electrode. The mass of the catalyst in the membrane electrode is calculated according to the mass ratio of Nafion to the catalyst. The amount of the precious metal iridium and precious metal ruthenium in the membrane electrode is calculated according to the content of the precious metal iridium and ruthenium in the catalyst.
[0080] According to one embodiment of the present disclosure, the step of hot pressing treatment includes performing the hot pressing process in a hot press, clamping the sprayed membrane electrode with two clean, large-area PTFE membrane materials to protect the membrane electrode from contamination, and then clamping the PTFE membrane material with the membrane electrode with two smooth metal plates. After the upper and lower modules of the hot press are heated to the preset hot pressing temperature and stabilized, the membrane electrode, PTFE membrane material and metal plate are placed in the hot press together, and the hot pressing pressure is controlled to be 1 to 10 bar, and the hot pressing time is 1 to 3 minutes; the hot pressing temperature is 100 to 130°C.
[0081] According to one embodiment of the present disclosure, the ternary composite catalyst is prepared by the following steps:
[0082] S1, mixing an iridium source, a ruthenium source, a non-precious metal source, a complexing agent and water, and reacting the resulting mixture to obtain a first material; wherein the pH of the mixture is 5 to 10, and the complexing agent is selected from C4 to C8 organic polyacids and soluble salts of C4 to C8 organic polyacids;
[0083] S2, separating the water in the first material to obtain a ternary composite catalyst precursor;
[0084] S3. calcining the ternary composite catalyst precursor in an oxygen-containing atmosphere.
[0085] According to an embodiment of the present disclosure, step S1 includes the following steps:
[0086] S1-1, mixing the iridium source, the first complexing agent and water for the first time and adjusting the pH to 5-10 to obtain a first mixture;
[0087] S1-2, mixing the ruthenium source, the second complexing agent and water for a second time and adjusting the pH to 5 to 10 to obtain a second mixture;
[0088] S1-3, mixing the non-metal source, the third complexing agent and water for a third time and adjusting the pH to 5 to 10 to obtain a third mixture;
[0089] S1-4, mix the first mixture, the second mixture and the third mixture to obtain the mixed material. The above-mentioned implementation can improve the uniformity of dispersion of the iridium source, ruthenium source and non-precious metal source in the mixed material; at the same time, precipitation in the solution can be avoided; the reaction process does not use highly corrosive solvents such as hydrochloric acid, providing a preparation method with simple operation and mild conditions. In a further implementation, in the preparation of the iridium ruthenium tin ternary composite catalyst, the pH in S1-1, S1-2 and S1-3 is preferably 7 to 8; in the preparation of the iridium ruthenium titanium ternary composite catalyst, the pH in S1-1, S1-2 and S1-3 is preferably 6 to 7.
[0090] According to one embodiment of the present disclosure, the iridium source is selected from one or more of chloroiridic acid and chloroiridic acid alkali metal salts; preferably, the chloroiridic acid alkali metal salt is selected from one or both of potassium chloroiridic acid and sodium chloroiridic acid; the chloroiridic acid may or may not contain crystal water, generally containing crystal water (such as having the formula H 2 IrCl 6 6H 2 O); the ruthenium source is a soluble salt of ruthenium, preferably one or both of ruthenium trichloride and ruthenium acetate; the titanium source is a soluble salt of titanium, preferably one or both of titanyl sulfate or titanium sulfate; the tin source is a soluble salt of tin and / or a soluble alkali metal stannate, preferably one or both of tin tetrachloride or sodium stannate.
[0091] According to one embodiment of the present disclosure, the first complexing agent, the second complexing agent and the third complexing agent are the same or different, and are independently selected from one or more of citric acid, tartaric acid, malic acid, succinic acid, sodium citrate, sodium tartrate, sodium malate and sodium succinate; preferably, the molar ratio of the first complexing agent to the iridium source calculated as iridium is 1.5-2.5:1; the molar ratio of the second complexing agent to the ruthenium source calculated as ruthenium is 1-2:1; the molar ratio of the third complexing agent to the non-precious metal source calculated as non-precious metal is 1.5-3:1.
[0092] In one embodiment, in the preparation of the iridium-ruthenium-titanium ternary composite catalyst, the molar ratio of the first complexing agent to the iridium source calculated in iridium is 1.5 to 2:1, preferably 1.6 to 1.8:1; preferably, the molar ratio of the second complexing agent to the ruthenium source calculated in ruthenium is 1 to 2:1, preferably 1.3 to 1.6:1; preferably, the molar ratio of the third complexing agent to the titanium source calculated in titanium is 1.5 to 3:1, preferably 2 to 2.5:1. The above embodiment can avoid precipitation in the solution, and at the same time is conducive to the catalyst having a lower overpotential and higher oxygen evolution activity.
[0093] In one embodiment, in the preparation of the iridium ruthenium tin ternary composite catalyst, the molar ratio of the first complexing agent to the iridium source calculated in iridium is 1.5 to 2.5:1, preferably 1.8 to 2.2:1; the molar ratio of the second complexing agent to the ruthenium source calculated in ruthenium is 1 to 2:1, preferably 1.5 to 1.8:1; the molar ratio of the third complexing agent to the tin source calculated in tin is 2 to 3:1, preferably 2.2 to 2.7:1. The above embodiment can avoid precipitation in the solution, and at the same time is conducive to the catalyst having a lower overpotential and higher oxygen evolution activity.
[0094] According to one embodiment of the present disclosure, in step S1, the molar ratio of the iridium source calculated in iridium, the non-precious metal source calculated in non-precious metal, and the ruthenium source calculated in ruthenium is (2-6): (1-5): 1. In a further embodiment, in preparing the iridium-ruthenium-titanium ternary composite catalyst, the molar ratio of the iridium source calculated in iridium, the titanium source calculated in titanium, and the ruthenium source calculated in ruthenium in step S1 is (2-5): (1.5-5): 1. In a further embodiment, in preparing the iridium-ruthenium-tin ternary composite catalyst, the molar ratio of the iridium source calculated in iridium, the tin source calculated in tin, and the ruthenium source calculated in ruthenium in step S1 is (2-6): (1-5): 1. The above embodiment is conducive to the catalyst having a lower overpotential and a higher oxygen evolution activity.
[0095] According to one embodiment of the present disclosure, in step S1, the reaction conditions include: temperature of 30-80°C, reaction time of 0.5-4h; optionally, in step S1, the pH of the mixture is 6-8; optionally, a pH regulator is added to adjust the pH of the mixture, and optionally, the pH regulator is selected from one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide and ammonia water. In a further embodiment, in the preparation of iridium ruthenium titanium ternary composite catalyst, the reaction conditions in step S1 include: temperature of 30-60°C, preferably 40-50°C; reaction time of 1-4h, preferably 2-3h; preferably, in step S1, the pH of the mixture is 6-7. In a further embodiment, in the preparation of the iridium, ruthenium, and tin ternary composite catalyst, in step S1, the reaction conditions include: a temperature of 50 to 80° C., preferably 60 to 70° C.; a reaction time of 0.5 to 4 h, preferably 1 to 2 h; optionally, in step S1, the pH of the mixed material is 7 to 8.
[0096] According to one embodiment of the present disclosure, in step S3, the conditions for the calcination treatment include: a calcination temperature of 300 to 450°C; and a calcination time of 1 to 5 hours. In a further embodiment, in the preparation of an iridium, ruthenium, and titanium ternary composite catalyst, in step S3, the conditions for the calcination treatment include: a calcination temperature of 350 to 450°C, preferably 380 to 400°C; and a calcination time of 2 to 5 hours, preferably 3 to 4 hours. In a further embodiment, in the preparation of an iridium, ruthenium, and tin ternary composite catalyst, in step S3, the conditions for the calcination treatment include: a calcination temperature of 300 to 400°C, preferably 340 to 370°C; and a calcination time of 1 to 3 hours.
[0097] According to one embodiment of the present disclosure, the method further comprises: washing the product obtained by the roasting treatment; the solvent used in the washing treatment is a mixed solution of alcohol and water, and the alcohol accounts for 10 to 95% by weight of the mixed solution, preferably 30 to 60% by weight;
[0098] Preferably, the alcohol is selected from one or more of methanol, ethanol, n-propanol and isopropanol.
[0099] The third aspect of the present disclosure provides the membrane electrode described in the first aspect of the present disclosure for use in a proton exchange membrane water electrolysis process.
[0100] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.
[0101] The raw materials used in the examples were all commercially available and were analytically pure unless otherwise specified. Chloroiridic acid or alkali metal chloroiridic acid salt was prepared as an aqueous solution with a concentration of 0.182 mol / L for use, or as a solution with a higher concentration for use.
[0102] The proton exchange membrane used in the embodiment is a proton exchange membrane with product number Nafion 117 purchased from Chemours; the cathode catalyst used is a 40wt% Pt / C catalyst purchased from Johnson Matthey.
[0103] Instruments, methods and conditions for TEM analysis: The model of the high-resolution transmission electron microscope (HRTEM) used in the present invention is JEM-2100 (HRTEM) (Japan Electron Co., Ltd.), and the test conditions of the high-resolution transmission electron microscope are: the acceleration voltage is 200 kV.
[0104] BET test method: In the present disclosure, the pore structure properties of the samples were measured by a Quantachrome AS-6B analyzer, and the specific surface area of the catalyst was obtained by the Brunauer-Emmett-Taller (BET) method.
[0105] The membrane electrode current and voltage were tested on an electrochemical workstation model PTC-05100EW.
[0106] The model of the X-ray fluorescence spectrometer (XRF) is Rigaku 3013 X-ray fluorescence spectrometer, and the X-ray fluorescence spectrometry analysis test conditions are: scanning time is 100 s, and the atmosphere is air.
[0107] The present disclosure detects the elements on the surface of the material by X-ray photoelectron spectroscopy (XPS). The X-ray photoelectron spectroscopy used is an ESCALab220i-XL X-ray electron spectrometer equipped with Avantage V5.926 software produced by VG Scientific. The X-ray photoelectron spectroscopy analysis test conditions are as follows: the excitation source is monochromatic A1Kα X-ray, the power is 330W, and the basic vacuum during the analysis test is 3×10 -9 In addition, the electron binding energy was calibrated using the C1s peak (284.3 eV) of elemental carbon.
[0108] Preparation Example 1 Catalyst Ir 0.50 Ru 0.10 Ti 0.40 O 2 Preparation
[0109] (1) taking 20 mL (3.64 mmol) of chloroiridic acid aqueous solution, weighing 1.05 g (5.47 mmol) of citric acid, stirring and mixing at room temperature, and adjusting the pH of the solution to between 6 and 7; wherein the molar ratio of the first complexing agent to the iridium source in terms of iridium is 1.5:1;
[0110] (2) weighing 0.15 g (0.73 mmol) of ruthenium trichloride and dissolving it in 5 ml of water, weighing 0.16 g (0.83 mmol) of citric acid, stirring and mixing at room temperature, and adjusting the pH of the solution to between 6 and 7; wherein the molar ratio of the second complexing agent to the ruthenium source in terms of ruthenium is 1.1:1;
[0111] (3) Weigh 0.73 g (2.92 mmol) of titanium sulfate and dissolve it in 10 ml of water, weigh 0.84 g (4.38 mmol) of citric acid, stir and mix at room temperature, and adjust the pH of the solution to between 6 and 7; wherein the molar ratio of the third complexing agent to the titanium source in terms of titanium is 2.5:1; the molar ratio of the iridium source in terms of iridium, the titanium source in terms of titanium, and the ruthenium source in terms of ruthenium is 5:4:1;
[0112] (4) mixing the three solutions of steps (1) to (3) and reacting them at 50° C. for 2 h;
[0113] (5) After cooling, spin-dry at 70°C and dry in an oven at 120°C for 8 h;
[0114] (6) After the catalyst is taken out and cooled, it is ground and laid flat on a porcelain boat. In an air atmosphere, the temperature is increased to 370°C at a rate of 2°C / min and maintained for 3 h;
[0115] (7) Cool to room temperature, add a certain amount of deionized water, perform ultrasonic washing, centrifuge (10000 rpm, 10 min), then wash with a 1:1 mixed solvent of ethanol and water, and centrifuge for 3 times (pH test paper detection is neutral), and place the centrifuge tube with the catalyst in a forced air drying oven (60°C) for 12 h to obtain a catalyst, which is recorded as DY-1.
[0116] Preparation Example 2 Catalyst Ir 0.55 Ru 0.11 Sn 0.34 O 2 Preparation
[0117] (1) taking 20 mL (3.64 mmol) of chloroiridic acid aqueous solution, weighing 1.05 g (5.47 mmol) of citric acid, stirring and mixing at room temperature, and adjusting the pH of the solution to between 7 and 8; wherein the molar ratio of the first complexing agent to the iridium source in terms of iridium is 1.5:1;
[0118] (2) weighing 0.15 g (0.73 mmol) of ruthenium trichloride and dissolving it in 5 ml of water, weighing 0.15 g (0.78 mmol) of citric acid, stirring and mixing at room temperature, and adjusting the pH of the solution to between 7 and 8; wherein the molar ratio of the second complexing agent to the ruthenium source in terms of ruthenium is 1.1:1;
[0119] (3) Weigh Na 2 SnO 3 ·3H 2 0.60 g (2.25 mmol) of O is dissolved in 10 ml of water, 1.40 g (7.29 mmol) of citric acid is weighed, and after stirring and mixing at room temperature, the pH of the solution is adjusted to between 7 and 8; wherein the molar ratio of the third complexing agent to the tin source calculated in terms of tin is 3.2:1; the molar ratio of the iridium source calculated in terms of iridium, the tin source calculated in terms of tin, and the ruthenium source calculated in terms of ruthenium is 5:3:1;
[0120] (4) mixing the three solutions of steps (1) to (3) and reacting them at 70° C. for 1 h;
[0121] (5) After cooling, spin-dry at 70°C and dry in an oven at 120°C for 8 h;
[0122] (6) After the catalyst is taken out and cooled, it is ground and laid flat on a porcelain boat. In an air atmosphere, the temperature is increased to 330°C at a rate of 2°C / min and maintained for 2 h.
[0123] (7) Cool to room temperature, add a certain amount of deionized water, perform ultrasonic washing, centrifuge (10000 rpm, 10 min), then wash with a 1:1 mixed solvent of ethanol and water, and centrifuge for 3 times (pH test paper detection is neutral), and place the centrifuge tube containing the catalyst in a forced air drying oven (60°C) for 12 h to obtain a catalyst, which is recorded as DY-2.
[0124] Preparation Example 3 Catalyst Ir 0.30 Ru 0.30 Ti 0.40 O 2 Preparation
[0125] The method is the same as that of Preparation Example 1, except that the molar ratio of chloroiridic acid, ruthenium trichloride and titanium sulfate is 3:3:4, and the catalyst is finally obtained, which is recorded as DY-3.
[0126] Preparation Example 4 Catalyst Ir 0.30 Ru 0.30 Sn 0.40 O 2 Preparation
[0127] The method is the same as that of Preparation Example 2, except that the molar ratio of chloroiridic acid, ruthenium trichloride and tin tetrachloride is 3:3:4, and the catalyst is finally obtained, which is recorded as DY-4.
[0128] Example 1
[0129] After cleaning, the Nafion 117 proton exchange membrane was cut into 7×7 cm 2 Size, actual spraying area is 5×5cm 2 ;
[0130] (1) Weigh 100 mg of the prepared DY-1 catalyst, add 14 mL of isopropanol and 6 mL of ultrapure water, then add 200 mg of 5 wt% Nafion solution, and perform ultrasonic treatment for 40 min in an ice bath at an ultrasonic power of 900 W;
[0131] (2) Weigh 100 mg of 40 wt% Pt / C catalyst, add 14 mL of isopropanol and 6 mL of ultrapure water, then add 500 mg of 5 wt% Nafion solution, and ultrasonicate for 30 min in an ice bath at an ultrasonic power of 600 W;
[0132] (3) Lay Nafion 117 flat on a vacuum table, press the mold on it, set the temperature of the vacuum table to 85° C., spray the slurry prepared in step (1) and step (2) on both sides of the Nafion 117 membrane in the order of anode first and cathode later, and control the amount of slurry sprayed according to the target loading amount. The actual spraying amount is calculated by the mass difference before and after spraying;
[0133] (4) Place the sprayed membrane electrode into a hot press for hot pressing. Set the hot pressing temperature to 120°C, the hot pressing pressure to 3 bar, and the hot pressing time to 2 min.
[0134] The iridium loading in the anode catalyst layer in this embodiment is 0.42 mg / cm 2 The ruthenium loading is 0.044 mg / cm 2 The platinum loading in the cathode catalyst layer is 0.09 mg / cm 2 .
[0135] Example 2
[0136] After cleaning, the Nafion 117 proton exchange membrane was cut into 7×7 cm 2 Size, actual spraying area is 5×5cm 2 ;
[0137] (1) Weigh 100 mg of the prepared DY-2 catalyst, add 14 mL of isopropanol and 6 mL of ultrapure water, then add 200 mg of 5 wt% Nafion solution, and perform ultrasonic treatment for 40 min in an ice bath at an ultrasonic power of 900 W;
[0138] (2) Weigh 100 mg of 40 wt% Pt / C catalyst, add 14 mL of isopropanol and 6 mL of ultrapure water, then add 500 mg of 5 wt% Nafion solution, and ultrasonicate for 30 min in an ice bath at an ultrasonic power of 600 W;
[0139] (3) Lay Nafion 117 flat on a vacuum table, press the mold on it, set the temperature of the vacuum table to 85° C., spray the slurry prepared in step (1) and step (2) on both sides of the Nafion 117 membrane in the order of anode first and cathode later, and control the amount of slurry sprayed according to the target loading amount. The actual spraying amount is calculated by the mass difference before and after spraying;
[0140] (3) The sprayed membrane electrode was placed in a hot press for hot pressing. The hot pressing temperature was set to 120°C, the hot pressing pressure was set to 3 bar, and the hot pressing time was set to 2 min.
[0141] In this embodiment, the iridium loading in the anode catalyst layer is 0.40 mg / cm 2 The ruthenium loading is 0.042 mg / cm 2 The platinum loading in the cathode catalyst layer is 0.10 mg / cm 2 .
[0142] Example 3
[0143] After cleaning, the Nafion 117 proton exchange membrane was cut into 7×7 cm 2 Size, actual spraying area is 5×5cm 2 ;
[0144] (1) Weigh 100 mg of the prepared DY-3 catalyst, add 14 mL of isopropanol and 6 mL of ultrapure water, then add 200 mg of 5 wt% Nafion solution, and perform ultrasonic treatment for 40 min in an ice bath at an ultrasonic power of 900 W;
[0145] (2) Weigh 100 mg of 40 wt% Pt / C catalyst, add 14 mL of isopropanol and 6 mL of ultrapure water, then add 500 mg of 5 wt% Nafion solution, and ultrasonicate for 30 min in an ice bath at an ultrasonic power of 600 W;
[0146] (3) Lay Nafion 117 flat on a vacuum table, press the mold on it, set the temperature of the vacuum table to 85° C., spray the slurry prepared in step (1) and step (2) on both sides of the Nafion 117 membrane in the order of anode first and cathode later, and control the amount of slurry sprayed according to the target loading amount. The actual spraying amount is calculated by the mass difference before and after spraying;
[0147] (4) Place the sprayed membrane electrode into a hot press for hot pressing, set the hot pressing temperature to 120°C, the hot pressing pressure to 3 bar, and the hot pressing time to 2 min.
[0148] The iridium loading in the anode catalyst layer in this embodiment is 0.32 mg / cm 2 The ruthenium loading is 0.17 mg / cm 2 The platinum loading in the cathode catalyst layer is 0.09 mg / cm 2 .
[0149] Example 4
[0150] After cleaning, the Nafion 117 proton exchange membrane was cut into 7×7 cm 2 Size, actual spraying area is 5×5cm 2 ;
[0151] (1) Weigh 100 mg of the prepared DY-4 catalyst, add 14 mL of isopropanol and 6 mL of ultrapure water, then add 200 mg of 5 wt% Nafion solution, and perform ultrasonic treatment for 40 min in an ice bath at an ultrasonic power of 900 W;
[0152] (2) Weigh 100 mg of 40 wt% Pt / C catalyst, add 14 mL of isopropanol and 6 mL of ultrapure water, then add 500 mg of 5 wt% Nafion solution, and ultrasonicate for 30 min in an ice bath at an ultrasonic power of 600 W;
[0153] (3) Lay Nafion 117 flat on a vacuum table, press the mold on it, set the temperature of the vacuum table to 85° C., spray the slurry prepared in steps (2) and (3) on both sides of the Nafion 117 membrane in the order of anode first and cathode later, and control the amount of slurry sprayed according to the target loading amount. The actual spraying amount is calculated by the mass difference before and after spraying;
[0154] (4) The sprayed membrane electrode was placed in a hot press for hot pressing. The hot pressing temperature was set to 120°C, the hot pressing pressure was set to 3 bar, and the hot pressing time was set to 2 min.
[0155] The iridium loading in the anode catalyst layer in this embodiment is 0.31 mg / cm 2 The ruthenium loading is 0.19 mg / cm 2 The platinum loading in the cathode catalyst layer is 0.10 mg / cm 2 .
[0156] Example 5
[0157] After cleaning, the Nafion 117 proton exchange membrane was cut into 7×7 cm 2Size, actual spraying area is 5×5cm 2 ;
[0158] (1) Weigh 100 mg of the prepared DY-1 catalyst, add 14 mL of isopropanol and 6 mL of ultrapure water, then add 200 mg of 5 wt% Nafion solution, and perform ultrasonic treatment for 40 min in an ice bath at an ultrasonic power of 900 W;
[0159] (2) Weigh 100 mg of 40 wt% Pt / C catalyst, add 14 mL of isopropanol and 6 mL of ultrapure water, then add 500 mg of 5 wt% Nafion solution, and ultrasonicate for 30 min in an ice bath at an ultrasonic power of 600 W;
[0160] (3) Lay Nafion 117 flat on a vacuum table, press the mold on it, set the temperature of the vacuum table to 85° C., spray the slurry prepared in steps (2) and (3) on both sides of the Nafion 117 membrane in the order of anode first and cathode later, and control the amount of slurry sprayed according to the target loading amount. The actual spraying amount is calculated by the mass difference before and after spraying;
[0161] (4) The sprayed membrane electrode was placed in a hot press for hot pressing. The hot pressing temperature was set to 90°C, the hot pressing pressure was set to 0.5 bar, and the hot pressing time was set to 2 min.
[0162] The loading amount of metal iridium in the anode catalyst layer in this embodiment is 0.42 mg / cm 2 The loading amount of ruthenium metal is 0.044 mg / cm 2 The loading amount of metal platinum in the cathode catalyst layer is 0.09 mg / cm 2 .
[0163] Example 6
[0164] (1) After cleaning the Nafion 117 proton exchange membrane, cut it into 7×7 cm 2 Size, actual spraying area is 5×5cm 2 ;
[0165] (2) Weigh 100 mg of the prepared DY-1 catalyst, add 14 mL of isopropanol and 6 mL of ultrapure water, then add 200 mg of 5 wt% Nafion solution, and perform ultrasonic treatment for 40 min in an ice bath at an ultrasonic power of 900 W;
[0166] (3) Weigh 100 mg of 40 wt% Pt / C catalyst, add 14 mL of isopropanol and 6 mL of ultrapure water, then add 500 mg of 5 wt% Nafion solution, and ultrasonicate for 30 min in an ice bath at an ultrasonic power of 600 W;
[0167] (4) Nafion 117 is spread flat on the vacuum table of the doctor blade coating machine, and the mold is pressed on. The temperature of the vacuum table is set to 85° C. The slurry prepared in step (2) and step (3) is successively doctor-coated on both sides of the Nafion 117 membrane in the order of anode first and cathode later, and the amount of the slurry to be doctor-coated is controlled according to the target loading amount. The actual amount of doctor-coating is calculated by the mass difference before and after doctor-coating;
[0168] (5) The coated membrane electrode was placed in a hot press for hot pressing. The hot pressing temperature was set to 120°C, the hot pressing pressure was set to 3 bar, and the hot pressing time was set to 2 min.
[0169] The loading amount of metal iridium in the anode catalyst layer in this embodiment is 0.82 mg / cm 2 The loading amount of ruthenium metal is 0.086 mg / cm 2 The loading amount of metal platinum in the cathode catalyst layer is 0.34 mg / cm 2 .
[0170] Comparative Example 1
[0171] Commercial iridium dioxide catalyst was purchased from Sigma Aldrich Company with product number 206237 and was recorded as D1.
[0172] After cleaning, the Nafion 117 proton exchange membrane was cut into 7×7 cm 2 Size, actual spraying area is 5×5cm 2 ;
[0173] (1) Weigh 100 mg of commercial D1 catalyst, add 14 mL of isopropanol and 6 mL of ultrapure water, then add 200 mg of 5 wt% Nafion solution, and ultrasonicate for 40 min in an ice bath at an ultrasonic power of 900 W;
[0174] (2) Weigh 100 mg of 40 wt% Pt / C catalyst, add 14 mL of isopropanol and 6 mL of ultrapure water, then add 500 mg of 5 wt% Nafion solution, and ultrasonicate for 30 min in an ice bath at an ultrasonic power of 600 W;
[0175] (3) Lay Nafion 117 flat on a vacuum table, press the mold on it, set the temperature of the vacuum table to 85° C., spray the slurry prepared in step (1) and step (2) on both sides of the Nafion 117 membrane in the order of anode first and cathode later, and control the amount of slurry sprayed according to the target loading amount. The actual spraying amount is calculated by the mass difference before and after spraying;
[0176] (4) The sprayed membrane electrode was placed in a hot press for hot pressing. The hot pressing temperature was set to 120°C, the hot pressing pressure was set to 3 bar, and the hot pressing time was set to 2 min.
[0177] In this embodiment, the iridium loading in the anode catalyst layer is 1.10 mg / cm 2 The platinum loading in the cathode catalyst layer is 0.13 mg / cm 2 .
[0178] The loading amounts of precious metals in the anode catalyst layer and the cathode precious metals in the above examples and comparative examples are listed in Table 1. The test results of the BET specific surface area and particle size of the catalysts in Preparation Examples 1 to 4 are also listed in Table 1.
[0179] Table 1
[0180]
[0181] According to the data in Table 1, we can see that:
[0182] Compared with the membrane electrode in comparative example 1, the membrane electrode in examples 1 to 6 has lower decomposition voltage, lower iridium loading, and lower ruthenium loading, indicating that the membrane electrode prepared using the catalyst provided by the present invention has low precious metal usage and good performance.
[0183] By comparing Example 1 with Example 6, it can be seen that the membrane electrode in Example 1 has a lower decomposition voltage, a lower iridium loading, and a lower ruthenium loading, indicating that the use of ultrasonic spraying can further reduce the amount of precious metals used and improve the performance of the membrane electrode compared to the traditional scraping method.
[0184] By comparing Example 1 with Example 5, it can be seen that the membrane electrode decomposition voltage in Example 1 is lower, indicating that within the range of hot pressing treatment conditions for preparing the membrane electrode disclosed in the present invention, the performance of the prepared membrane electrode is better.
[0185] By comparing Example 2 with Example 4, it can be seen that the membrane electrode in Example 4 has a lower decomposition voltage, a lower iridium loading, and a lower ruthenium loading, indicating that within the composition range of the iridium, ruthenium, and tin ternary composite catalyst disclosed in the present invention, the prepared membrane electrode has a low amount of precious metals and good performance.
[0186] By comparing Example 1 with Example 3, it can be seen that the membrane electrode in Example 1 has a lower decomposition voltage, a lower iridium loading, and a lower ruthenium loading, indicating that within the composition range of the iridium ruthenium titanium ternary composite catalyst disclosed in the present invention, the prepared membrane electrode has a low precious metal dosage and good performance.
[0187] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0188] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0189] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A proton exchange membrane water electrolysis membrane electrode, the membrane electrode comprising an anode catalyst layer, characterized in that: The anode catalyst layer comprises a ternary composite catalyst containing iridium and ruthenium, wherein the ternary composite catalyst comprises iridium, ruthenium and non-precious metal elements, and the XRD spectrum of the ternary composite catalyst only shows an amorphous peak package at 25-40°; Wherein, the non-precious metal element includes one or both of tin and titanium.
2. The membrane electrode according to claim 1, wherein: The O1s characteristic peak of the XPS spectrum of the ternary composite catalyst includes a MO characteristic peak and an M-OH characteristic peak, and B0 defined by the following formula (1) is any value between 0.2 and 0.5; B0=B1 / (B1+B2) Formula (1); Wherein, B1 is the peak area of the M-OH characteristic peak in the XPS spectrum of the ternary composite catalyst, and B2 is the peak area of the MO characteristic peak in the XPS spectrum of the ternary composite catalyst.
3. The membrane electrode according to claim 1, wherein: The BET specific surface area of the ternary composite catalyst is 50 to 80 m 2 / g, particle size is 2 to 10 nm.
4. The membrane electrode according to claim 1, wherein: The XRD spectrum of the ternary composite catalyst has no crystal plane diffraction peaks of iridium dioxide, ruthenium dioxide and non-noble metal oxides.
5. The membrane electrode according to claim 1, wherein: The composition of the ternary composite catalyst includes: relative to the total molar number of metal elements, the molar number of Ir is 0.4-0.6, and the molar number of Ru is 0.1-0.
2.
6. The membrane electrode according to any one of claims 1 to 5, wherein: The ternary composite catalyst comprises an iridium-ruthenium-titanium ternary composite catalyst, and the chemical composition of the iridium-ruthenium-titanium ternary composite catalyst is Ir x Ru y Ti 1-x-y O2; x is any value between 0.4 and 0.5, and y is any value between 0.1 and 0.2; The BET specific surface area of the iridium, ruthenium and titanium ternary composite catalyst is 50 to 60 m 2 / g, particle size is 2~10nm; The B0 of the XPS spectrum of the iridium, ruthenium and titanium ternary composite catalyst is any value between 0.2 and 0.3; The XRD spectrum of the iridium, ruthenium and titanium ternary composite catalyst only shows an amorphous peak package at 30-40 degrees.
7. The membrane electrode according to any one of claims 1 to 5, wherein: The ternary composite catalyst comprises an iridium-ruthenium-tin ternary composite catalyst, and the chemical composition of the iridium-ruthenium-tin ternary composite catalyst is Ir m Ru n Sn 1-m-n O2; wherein m is any value between 0.4 and 0.6, and n is any value between 0.1 and 0.2; The BET specific surface area of the iridium, ruthenium, and tin ternary composite catalyst is 60 to 80 m 2 / g, particle size is 3-8nm; The B0 of the XPS spectrum of the iridium, ruthenium, and tin ternary composite catalyst is any value between 0.4 and 0.5; The XRD spectrum of the iridium, ruthenium and tin ternary composite catalyst only shows an amorphous peak package between 25° and 40°.
8. The membrane electrode according to claim 1, wherein: The iridium loading in the anode catalyst layer is 0.1 to 0.5 mg / cm 2 ; The ruthenium loading is 0.01~0.06mg / cm 2 .
9. The membrane electrode according to claim 1, wherein: The membrane electrode further comprises a proton exchange membrane and a cathode catalyst layer. The anode catalyst layer and the cathode catalyst layer are respectively stacked on both sides of the proton exchange membrane.
10. A method for preparing a proton exchange membrane water electrolysis membrane electrode according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: An anode catalyst layer containing the ternary composite catalyst is formed on the first main surface of the proton exchange membrane; a cathode catalyst layer is formed on the second main surface of the proton exchange membrane; and the obtained membrane electrode precursor is subjected to hot pressing treatment.
11. The method according to claim 10, wherein: The step of forming the anode catalyst layer comprises: preparing an anode catalyst layer slurry containing the ternary composite catalyst and performing a first ultrasound; spraying the anode catalyst layer slurry on the first main surface of the proton exchange membrane by ultrasonic spraying; The step of forming the cathode catalyst layer comprises: preparing cathode catalyst layer slurry and performing a second ultrasound; spraying the cathode catalyst layer slurry on the second main surface of the proton exchange membrane by ultrasonic spraying; The anode catalyst layer slurry includes a ternary composite catalyst, a Nafion solution and a dispersant solution; wherein, in the anode catalyst layer slurry, the mass fraction of the ternary composite catalyst is 0.1-2wt%, preferably 0.5-1wt%; the mass fraction of the Nafion solution is 5-12%, preferably 9-11%; the dispersant solution is a mixed solution of water and isopropanol; the volume fraction of the isopropanol in the mixed solution is 60-80%, preferably 70-75%.
12. The method according to claim 11, wherein: The first ultrasonic conditions include: ultrasonic time of 20 to 60 minutes, ultrasonic power of 600 to 900 W; The second ultrasonic conditions include: ultrasonic time of 20 to 60 minutes, ultrasonic power of 600 to 900W; The conditions of the hot pressing treatment include: hot pressing temperature of 100-130°C, hot pressing pressure of 1-10 bar, and hot pressing time of 1-3 min.
13. The method according to claim 10, wherein: The ternary composite catalyst is prepared by the following steps: S1, mixing an iridium source, a ruthenium source, a non-precious metal source, a complexing agent and water, and reacting the resulting mixture to obtain a first material; wherein the pH of the mixture is 5 to 10, and the complexing agent is selected from C4 to C8 organic polyacids and soluble salts of C4 to C8 organic polyacids; S2, separating the water in the first material to obtain a ternary composite catalyst precursor; S3. calcining the ternary composite catalyst precursor in an oxygen-containing atmosphere.
14. The method according to claim 13, wherein: In step S1, the molar ratio of the iridium source calculated as iridium, the non-precious metal source calculated as non-precious metal, and the ruthenium source calculated as ruthenium is (2-6): (1-5): 1; In step S1, the reaction conditions include: temperature of 30-80°C, reaction time of 0.5-4h; Optionally, in step S1, the pH of the mixed material is 6-8; In step S3, the conditions of the calcination treatment include: a calcination temperature of 300 to 450° C.; and a calcination time of 1 to 5 hours.
15. The method according to claim 13, wherein: Step S1 includes the following steps: S1-1, mixing the iridium source, the first complexing agent and water for the first time and adjusting the pH to 5-10 to obtain a first mixture; S1-2, mixing the ruthenium source, the second complexing agent and water for a second time and adjusting the pH to 5 to 10 to obtain a second mixture; S1-3, mixing the non-metal source, the third complexing agent and water for a third time and adjusting the pH to 5 to 10 to obtain a third mixture; S1-4, mixing the first mixture, the second mixture and the third mixture to obtain the mixed material.
16. The method according to claim 15, wherein: The iridium source is selected from one or more of chloroiridic acid and chloroiridic acid alkali metal salts; preferably, the chloroiridic acid alkali metal salt is selected from one or two of potassium chloroiridate and sodium chloroiridate; The ruthenium source is a soluble salt of ruthenium, preferably one or both of ruthenium trichloride and ruthenium acetate; The non-metallic source includes one or both of a titanium source and a tin source; the titanium source is a soluble salt of titanium, preferably one or both of titanyl sulfate or titanium sulfate; the tin source is a soluble salt of tin and / or a soluble alkali metal stannate, preferably one or both of tin tetrachloride or sodium stannate; The first complexing agent, the second complexing agent and the third complexing agent are the same or different, and are independently selected from one or more of citric acid, tartaric acid, malic acid, succinic acid, sodium citrate, sodium tartrate, sodium malate and sodium succinate; Preferably, the molar ratio of the first complexing agent to the iridium source is 1.5 to 2.5:1; Preferably, the molar ratio of the second complexing agent to the ruthenium source calculated as ruthenium is 1 to 2:1; Preferably, the molar ratio of the third complexing agent to the non-precious metal source calculated as non-precious metal is 1.5 to 3:
1.
17. The membrane electrode according to any one of claims 1 to 9 is used in a proton exchange membrane water electrolysis process.